Innovative Jominy Test Equipment for Evaluating The Hardening Of AISI 1045 Steel - Rahman; Arif, Zainal; Suheri; Bahri Widodo, Syamsul (Fakultas Teknik Universitas Samudra, 2024)
The development of heat treatment testing equipment is essential in metallurgical applications, especially for determining the hardenability of steel. This study focuses on designing a portable Jominy test apparatus to evaluate the hardenability of AISI 1045 medium carbon steel, offering a more practical and cost-effective solution. The apparatus was built with an angle iron frame (64 x 82 x 64 cm) and equipped with a 200-liter water drum and a Shimizu water pump (18 L/min flow rate). Hardness testing was performed using the Rockwell B method (150 kgf load, 15-second dwell) on specimens subjected to three conditions: raw, water-quenched, and oil-quenched, after heating at 900 °C for 30 minutes. The results showed hardness increases from 91.00 HRB (raw) to 101.33 HRB (water-quenched) and 100.33 HRB (oil-quenched), with water quenching producing slightly higher values due to its faster cooling rate. The study demonstrates the effectiveness of the portable apparatus for evaluating AISI 1045 steel hardenability with advantages in portability, cost, and reliability.